2021
DOI: 10.1007/s10493-021-00635-1
|View full text |Cite
|
Sign up to set email alerts
|

Mite communities (Acari: Mesostigmata, Oribatida) in the red belt conk, Fomitopsis pinicola (Polyporales), in Polish forests

Abstract: The fruiting bodies of bracket fungi are a specific microhabitat colonized by various invertebrates of which mites (Acari) are rarely studied, and if they are, the study is usually faunistic. The aim of the research was to determine whether the diversification of mite assemblages (Mesostigmata, Oribatida) inhabiting the fruiting bodies of Fomitopsis pinicola (Sw.) P. Karst. (Polyporales) are connected with the character of the forests and/or the degree of decay (DD) of the fruiting bodies. The research was con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 53 publications
(74 reference statements)
0
3
0
Order By: Relevance
“…Most Polyporales have shiny surfaces of a woody nature, owing to the pigmentation on the surface, and they are highly suitable for the development of mushroom-based biomaterials [ 10 ]. They are distributed widely in the forest ecosystem, where they decompose deadwood, recycling major nutrients in the system [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most Polyporales have shiny surfaces of a woody nature, owing to the pigmentation on the surface, and they are highly suitable for the development of mushroom-based biomaterials [ 10 ]. They are distributed widely in the forest ecosystem, where they decompose deadwood, recycling major nutrients in the system [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…These natural biomaterials will be replaced with various petroleum-based products to reduce the intolerable stress placed on the planet’s environment. Recently, many studies have shown the potential of developing packaging, building, textile, and transparent edible films using fungi/mushrooms [ 17 , 19 ]. However, few studies have been conducted on MBL production and processing.…”
Section: Discussionmentioning
confidence: 99%
“…This actually maintains the species richness of the oribatids. Such fungi are less abundant in areas under forest management, which implies that they are more speciespoor compared to forests without human intervention (Gdula et al, 2021). However, both the number of individuals and the number of species are lower in disturbed areas than in places where natural vegetation is still present and there is no human disturbance.…”
Section: Ecological Indicationmentioning
confidence: 99%
“…The mite fauna of living macrofungi may, in parts, be different from that of dead or decaying fungi (Hagvar & Steen, 2013;Gdula et al, 2021b;Gdula et al, 2022). We expect some overlap with oribatid mites from soil, especially stressed soil.…”
mentioning
confidence: 94%